Rethinking Development : Challenges and Opportunities - Wolfensohn, James D. (2017)
James D. Wolfensohn, President of the World Bank Group, discussed his vision for development, addressing these topics: poverty and the development agenda; rethinking the approach; the global trading system and the development agenda; and the partnership imperative. He concludes that the Bank must work to realize an ambitious vision if we are to go forward together into a new century in which the long pent up aspirations of the poor of the earth are to have the chance for fulfillment that they deserve.